Optical coating material with high light transmission performance and preparation method thereof
Optical coating materials are prepared through the combination of aluminum powder, titanium oxide, dilanthanum trioxide, rare earth fluoride and polymer, which solves the problem of poor stability of traditional materials under long-term use, and achieves the combination of high light transmission performance and long-term stability.
Patent Information
- Application Number
- CN202411672010.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional optical coating materials have poor stability and obvious performance attenuation in long-term use or harsh environments, making it difficult to meet the requirements of high-precision and high stability of high-end optical equipment.
Optical coating materials are prepared by high-temperature sintering, vacuum melting and cooling crystallization steps using a combination of aluminum powder, titanium oxide, dilanthanum trioxide, rare earth fluoride and polymer.
The prepared optical coating materials maintain high light transmission performance, and have good stability and durability. They can maintain good performance for a long time and meet the requirements of optical parts and equipment.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical coating, and in particular to an optical coating material with high light transmittance and a preparation method thereof. Background Art
[0002] Optical coating refers to the process of coating one or more layers of metal or dielectric films on the surface of optical parts in order to reduce or increase the reflection, beam splitting, color separation, light filtering, polarization, etc. of light. By coating a layer of transparent electrolyte film on the surface of the material, the reflection and transmission characteristics of the material surface are changed. Common coating methods include vacuum coating and chemical coating.
[0003] Optical coating materials are materials used to form thin film layers on the surface of optical parts. They usually have high transparency, optical uniformity and chemical stability. Through the combination of different optical coating materials, specific optical effects can be controlled and thus applied to different fields, such as optical lenses, filters, optical thin film coatings, etc.
[0004] Traditional optical coating materials have the following problems during use: optical materials have poor stability and obvious performance degradation under long-term use or in harsh environments. Due to the limitations of formulation and process, traditional optical coating materials often sacrifice durability while improving light transmittance, making it difficult to meet the strict requirements of high-end optical equipment for high precision and high stability. Summary of the invention
[0005] In order to provide an optical coating material with high light transmittance and long-term stability, the present application provides an optical coating material with high light transmittance and a preparation method thereof.
[0006] The present application provides an optical coating material with high light transmittance and a preparation method thereof using the following technical solutions: In a first aspect, the present application provides an optical coating material with high light transmittance, comprising the following raw materials in parts by weight: 50-60 parts of aluminum powder; 20-28 parts of titanium dioxide; 4-10 parts of lanthanum trioxide; 2-6 parts of rare earth fluoride; 1-3 parts of polymer.
[0007] By adopting the above technical scheme and selecting a combination of aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer, the prepared optical coating material maintains a relatively high light transmittance. At the same time, the optical coating material has good stability and durability, and can maintain good performance for a long time, meeting the requirements of optical parts and equipment.
[0008] Aluminum powder and titanium dioxide are selected as the main substances, so that the optical coating material has good strength, is not easy to be scratched, and has good transmittance of visible light; the doping of lanthanum trioxide can affect the lattice of titanium dioxide and expand the light absorption range of the optical coating material; the addition of rare earth fluoride is beneficial to improve the adhesion between the optical coating material and the substrate, thereby improving the stability; the addition of polymer makes the coating more uniform and improves the corrosion resistance. Through overall coordination, the coating is made uniform and stable, avoiding the problem of film shedding or scratches.
[0009] In a preferred embodiment, the rare earth fluoride is selected from one or more of yttrium fluoride, cerium fluoride, ytterbium fluoride, and scandium fluoride.
[0010] By adopting the above technical solution, the addition of rare earth fluoride makes the film layer of the optical coating material more uniform and dense, and enhances the adhesion between the film layer and the base layer, making it more stable on the surface of the optical part.
[0011] In a preferred embodiment, the rare earth fluoride is a mixture of yttrium fluoride and cerium fluoride, and the weight ratio of the yttrium fluoride to the cerium fluoride is 1:(0.4-0.7).
[0012] By adopting the above technical solution, it was found in the experiment that the comprehensive performance of the optical coating material film layer, such as light transmittance, color, adhesion, etc., is better through a specific proportion of yttrium fluoride and cerium fluoride.
[0013] In a preferred embodiment, the polymer is selected from one or more of polyvinyl alcohol, polyimide, and polyethyl methacrylate.
[0014] By adopting the above technical solution, polymers are selected and added to the optical coating material. On the one hand, the polymer is beneficial to the mixed bonding of aluminum powder, titanium dioxide, lanthanum trioxide and rare earth fluoride, thereby improving the compatibility of the materials and being beneficial to the uniformity of the coating material. On the other hand, the addition of the polymer is beneficial to protecting the coating, reducing the pollution and corrosion of the coating by substances in the environment, and enhancing the stability and service life of the coating.
[0015] In a preferred embodiment, the polymer is a mixture of polyvinyl alcohol and polyimide, and the weight ratio of the polyvinyl alcohol to the polyimide is 1:(0.3-0.5).
[0016] By adopting the above technical solution, polyvinyl alcohol and polyimide in a specific proportion are selected to have excellent bonding strength, and at the same time have good water resistance and weather resistance, so that the comprehensive performance of the optical coating material is better.
[0017] In a preferred embodiment, the particle sizes of the aluminum powder, the titanium dioxide, the lanthanum trioxide and the rare earth fluoride are 0.2-0.8 μm.
[0018] By adopting the above technical solution and limiting the particle size of the material, the film layer of the optical coating material is made uniform and dense.
[0019] In a second aspect, the present application provides a method for preparing an optical coating material with high light transmittance, comprising the following steps: (1) Mixing raw materials: weighing aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer according to weight, putting them into a mixing device, and stirring to obtain a mixture; (2) High temperature sintering: the mixed material is placed in a crucible, the crucible is placed in a high temperature sintering furnace, and the temperature is increased under oxygen conditions for high temperature sintering; (3) Vacuum melting: Turn on the vacuum system, continue to increase the temperature, and introduce argon gas to melt the raw materials; (4) Cooling and crystallization: maintaining the temperature for a period of time, slowly cooling down, and taking out the crystals to obtain the optical coating material.
[0020] By adopting the above technical scheme, an optical coating material is prepared through the steps of raw material mixing, high-temperature sintering, vacuum melting and cooling crystallization, providing a new type of optical coating material with high light transmittance and long-term stability.
[0021] In a preferred embodiment, in step (2), the temperature is raised to 400-650° C. and maintained for 2-3 hours.
[0022] By adopting the above technical solution and limiting the temperature, the polymer is completely degraded during the high-temperature sintering process to form a uniform film layer with good compatibility.
[0023] In a preferred embodiment, in step (3), the vacuum degree in the high-temperature sintering furnace is evacuated to 8×10-4-10-3Pa, and when the temperature rises to 1200-1400°C, argon is introduced, and the temperature is continued to rise to 1700-1800°C at a rate of 8-12°C / min and maintained for 3-5h.
[0024] By adopting the above technical solution, the vacuum degree and temperature are controlled during the vacuum melting process, so as to reduce the loss of materials during the coating process, improve the utilization rate of materials, enhance the uniformity and aggregation density of the coating, and prevent spots from being generated in the film layer when releasing oxygen.
[0025] In a preferred embodiment, in step (4), the cooling rate is 20-35°C / h, and the temperature is finally reduced to 20-30°C.
[0026] By adopting the above technical solution, the cooling rate during the cooling and crystallization process is controlled to ensure the precipitation effect and facilitate the control of the film thickness.
[0027] In summary, the present application has at least one of the following beneficial effects: 1. By selecting a combination of aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer, the prepared optical coating material maintains a high light transmittance. At the same time, the optical coating material has good stability and durability, can maintain good performance for a long time, and meet the requirements of optical parts equipment.
[0028] Aluminum powder and titanium dioxide are selected as the main substances, so that the optical coating material has good strength, is not easy to be scratched, and has good transmittance of visible light; the doping of lanthanum trioxide can affect the lattice of titanium dioxide and expand the light absorption range of the optical coating material; the addition of rare earth fluoride is beneficial to improve the adhesion between the optical coating material and the substrate, thereby improving the stability; the addition of polymer makes the coating more uniform and improves the corrosion resistance. Through overall coordination, the coating is made uniform and stable, avoiding the problem of film shedding or scratches.
[0029] 2. The addition of rare earth fluoride makes the film layer of the optical coating material more uniform and dense, and enhances the adhesion between it and the base layer, making it more stable on the surface of optical parts.
[0030] 3. Select polymers to be added to optical coating materials. On the one hand, polymers are beneficial to the mixed bonding of aluminum powder, titanium dioxide, lanthanum trioxide and rare earth fluorides, thereby improving the compatibility of materials and promoting the uniformity of coating materials. On the other hand, the addition of polymers is beneficial to protecting the coating, reducing the pollution and corrosion of the coating by substances in the environment, and enhancing the stability and service life of the coating. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with Examples 1-8.
[0032] Aluminum powder was purchased from Shenzhen Qiushan Industrial Equipment Co., Ltd. with a purity of 99.999%.
[0033] Titanium dioxide was purchased from Hefei AVIC Nanotechnology Development Co., Ltd. with a purity of 99.99%.
[0034] Lanthanum trioxide was purchased from Qinghe County Ruijiang Metal Materials Co., Ltd. with a purity of 99.99%.
[0035] Yttrium fluoride was purchased from Hubei Xinhongyu Biomedical Technology Co., Ltd. with a purity of 99.9%.
[0036] Cerium fluoride was purchased from Jining Juji New Materials Co., Ltd. with a purity of 99.95%.
[0037] Scandium fluoride was purchased from Hebei Teng Bimetallic Materials Co., Ltd. with a purity of 99.99%.
[0038] The particle sizes of aluminum powder, titanium dioxide, lanthanum trioxide, yttrium fluoride, cerium fluoride and scandium fluoride are all 0.2-0.8 μm. Example
[0039] Example 1 This embodiment discloses an optical coating material with high light transmittance, comprising the following raw materials in parts by weight: 50 parts of aluminum powder; 20 parts of titanium dioxide; 4 parts of lanthanum trioxide; Rare earth fluoride, specifically 2 parts of yttrium fluoride; The polymer is specifically selected from 1 part of polyimide.
[0040] A method for preparing an optical coating material with high light transmittance comprises the following steps: (1) Mixing raw materials: weighing aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer according to weight, putting them into a mixing device, and stirring to obtain a mixture; (2) High temperature sintering: the mixed material is loaded into a crucible and compacted, and the crucible is placed in a high temperature sintering furnace. The temperature in the high temperature sintering furnace is increased to 400° C. and maintained for 2 h under oxygen conditions for high temperature sintering; (3) Vacuum melting: Turn on the vacuum system and evacuate until the vacuum degree in the high-temperature sintering furnace reaches 8×10 -4 Pa, after heating to 1200℃, argon gas was introduced into the high-temperature sintering furnace, and the temperature was continued to rise to 1700℃ at a rate of 8℃ / min and maintained for 3h; (4) Cooling and crystallization: Slowly cool the temperature at a rate of 20°C / h, wait for the crystals to grow in the crucible, and finally cool the temperature to 20°C, take out the crystals to obtain the optical coating material.
[0041] Example 2 This embodiment discloses an optical coating material with high light transmittance, comprising the following raw materials in parts by weight: 60 parts of aluminum powder; 28 parts of titanium dioxide; 10 parts of lanthanum trioxide; Rare earth fluoride, specifically 6 parts of scandium fluoride; The polymer is specifically selected from 3 parts of polyvinyl alcohol.
[0042] A method for preparing an optical coating material with high light transmittance comprises the following steps: (1) Mixing raw materials: weighing aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer according to weight, putting them into a mixing device, and stirring to obtain a mixture; (2) High temperature sintering: the mixed material is loaded into a crucible and compacted, and the crucible is placed in a high temperature sintering furnace. The temperature in the high temperature sintering furnace is increased to 650° C. and maintained for 3 h under oxygen conditions for high temperature sintering; (3) Vacuum melting: Turn on the vacuum system and evacuate until the vacuum degree in the high-temperature sintering furnace reaches 9×10 -4 Pa, after heating to 1400℃, argon gas was introduced into the high-temperature sintering furnace, and the temperature was continued to rise to 1800℃ at a rate of 12℃ / min and maintained for 5h; (4) Cooling and crystallization: Slowly cool the temperature at a rate of 35°C / h, wait for the crystals to grow in the crucible, and finally cool the temperature to 30°C, take out the crystals to obtain the optical coating material.
[0043] Example 3 This embodiment discloses an optical coating material with high light transmittance, comprising the following raw materials in parts by weight: Aluminum powder 55 parts; 23 parts of titanium dioxide; 7 parts of lanthanum trioxide; Rare earth fluoride, specifically 5 parts of cerium fluoride; The polymer is specifically selected from 2 parts of polyethyl methacrylate.
[0044] A method for preparing an optical coating material with high light transmittance comprises the following steps: (1) Mixing raw materials: weighing aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer according to weight, putting them into a mixing device, and stirring to obtain a mixture; (2) High temperature sintering: the mixed material is loaded into a crucible and compacted, and the crucible is placed in a high temperature sintering furnace. The temperature in the high temperature sintering furnace is increased to 500° C. and maintained for 2.5 h under oxygen conditions for high temperature sintering; (3) Vacuum melting: Turn on the vacuum system and vacuumize until the vacuum degree in the high-temperature sintering furnace reaches 10 -3 Pa, after heating to 1300℃, argon gas was introduced into the high-temperature sintering furnace, and the temperature was continued to rise to 1800℃ at a rate of 10℃ / min and maintained for 4h; (4) Cooling and crystallization: Slowly cool the temperature at a rate of 30°C / h, wait for the crystals to grow in the crucible, and finally cool the temperature to 25°C, take out the crystals to obtain the optical coating material.
[0045] Example 4 The only difference between this embodiment and embodiment 3 is that the rare earth fluoride in the raw material is different.
[0046] The rare earth fluoride in this embodiment is a mixture of yttrium fluoride and cerium fluoride, specifically 3.5 parts of yttrium fluoride and 1.5 parts of cerium fluoride.
[0047] The preparation method of an optical coating material with high light transmittance is the same as that in Example 3.
[0048] Example 5 The only difference between this embodiment and embodiment 3 is that the rare earth fluoride in the raw material is different.
[0049] The rare earth fluoride in this embodiment is a mixture of yttrium fluoride and cerium fluoride, specifically 3 parts of yttrium fluoride and 2 parts of cerium fluoride.
[0050] The preparation method of an optical coating material with high light transmittance is the same as that in Example 3.
[0051] Example 6 The only difference between this embodiment and embodiment 3 is that the polymers in the raw materials are different.
[0052] The polymer in this embodiment is a mixture of polyvinyl alcohol and polyimide, specifically 1.5 parts of polyvinyl alcohol and 0.5 parts of polyimide.
[0053] The preparation method of an optical coating material with high light transmittance is the same as that in Example 3.
[0054] Example 7 The only difference between this embodiment and embodiment 3 is that the polymers in the raw materials are different.
[0055] The polymer in this embodiment is a mixture of polyvinyl alcohol and polyimide, specifically 1.34 parts of polyvinyl alcohol and 0.66 parts of polyimide.
[0056] The preparation method of an optical coating material with high light transmittance is the same as that in Example 3.
[0057] Example 8 The only difference between this embodiment and embodiment 3 is that the rare earth fluoride and polymer in the raw materials are different.
[0058] The rare earth fluoride in this embodiment is a mixture of yttrium fluoride and cerium fluoride, specifically 3 parts of yttrium fluoride and 2 parts of cerium fluoride; the polymer is a mixture of polyvinyl alcohol and polyimide, specifically 1.5 parts of polyvinyl alcohol and 0.5 parts of polyimide.
[0059] The preparation method of an optical coating material with high light transmittance is the same as that in Example 3.
[0060] Performance Testing The optical coating material obtained in Example 1-8 was subjected to coating. The coating conditions were: electron beam evaporation equipment, evaporation rate 2.0 A / S, vacuum degree 1.5×10 -4 torr, substrate temperature 200℃, and optical coating was obtained.
[0061] Light transmittance: The light transmittance of each optical coating was tested by a light transmittance / haze meter, and the light transmittance results were recorded in Table 1.
[0062] Adhesion: The bonding strength of the film layer on the substrate surface is tested according to GB / T 28786-2012 "Vacuum technology vacuum coating layer bonding strength measurement method tape sticking method".
[0063] Corrosion resistance: Immerse each optical coating in a 1mmol / L concentrated nitric acid solution for 200 hours, then take it out and observe whether there are any corrosion spots on the film surface.
[0064] Table 1 Sample Light transmittance / % Adhesion / Grade Corrosion resistance Example 1 96.2 1 none Example 2 96.5 1 none Example 3 96.3 1 none Example 4 97.0 0 none Example 5 97.2 0 none Example 6 96.8 1 none Example 7 96.7 1 none Example 8 97.8 0 none According to Table 1, the optical coating material prepared in the present application has high light transmittance, high density and uniformity, and the formed optical coating has good adhesion to the substrate material and excellent corrosion resistance. Therefore, the optical coating material of the present application has excellent stability and durability while maintaining high light transmittance through a specific raw material formula and preparation method, and can meet the requirements of optical equipment.
[0065] When the rare earth fluoride is selected to be yttrium fluoride and cerium fluoride in a specific ratio, it is more conducive to improving the adhesion between the optical coating material and the substrate, while improving the uniformity of the optical coating material, which is conducive to improving the transmittance.
[0066] When the polymer uses polyvinyl alcohol and polyimide in a specific proportion, the compatibility of the overall raw materials is better, the optical coating material is more uniform during coating, and the bonding performance is improved, which is beneficial to the adhesion to the substrate, thereby improving the performance of the optical coating material.
[0067] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An optical coating material with high light transmittance, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of aluminum powder; 20-28 parts of titanium dioxide; 4-10 parts of lanthanum trioxide; 2-6 parts of rare earth fluoride; 1-3 parts of polymer.
2. The optical coating material with high light transmittance according to claim 1, characterized in that: The rare earth fluoride is selected from one or more of yttrium fluoride, cerium fluoride, ytterbium fluoride and scandium fluoride.
3. The optical coating material with high light transmittance according to claim 1, characterized in that: The rare earth fluoride is a mixture of yttrium fluoride and cerium fluoride, and the weight ratio of the yttrium fluoride to the cerium fluoride is 1:(0.4-0.7).
4. The optical coating material with high light transmittance according to claim 1, characterized in that: The polymer is selected from one or more of polyvinyl alcohol, polyimide, and polyethyl methacrylate.
5. The optical coating material with high light transmittance according to claim 1, characterized in that: The polymer is a mixture of polyvinyl alcohol and polyimide, and the weight ratio of the polyvinyl alcohol to the polyimide is 1:(0.3-0.5).
6. The optical coating material with high light transmittance according to claim 1, characterized in that: The particle sizes of the aluminum powder, the titanium dioxide, the lanthanum trioxide and the rare earth fluoride are 0.2-0.8 μm.
7. A method for preparing an optical coating material with high light transmittance according to any one of claims 1 to 6, characterized in that: The steps include: (1) Mixing raw materials: weighing aluminum powder, titanium dioxide, lanthanum trioxide, rare earth fluoride and polymer according to weight, putting them into a mixing device, and stirring to obtain a mixture; (2) High temperature sintering: the mixed material is placed in a crucible, the crucible is placed in a high temperature sintering furnace, and the temperature is increased under oxygen conditions for high temperature sintering; (3) Vacuum melting: Turn on the vacuum system, continue to increase the temperature, and introduce argon gas to melt the raw materials; (4) Cooling and crystallization: After keeping the temperature for a period of time, slowly cooling down, taking out the crystals to obtain the optical coating material.
8. The method for preparing an optical coating material with high light transmittance according to claim 7, characterized in that: In step (2), the temperature is raised to 400-650°C and maintained for 2-3 hours.
9. The method for preparing an optical coating material with high light transmittance according to claim 7, characterized in that: In step (3), the vacuum in the high temperature sintering furnace is evacuated to a vacuum degree of 8×10 -4 -10 -3 Pa, when the temperature rises to 1200-1400℃, introduce argon, continue to heat to 1700-1800℃ at a rate of 8-12℃ / min, and maintain for 3-5h.
10. The method for preparing an optical coating material with high light transmittance according to claim 8, characterized in that: In step (4), the cooling rate is 20-35°C / h, and the temperature is finally reduced to 20-30°C.